An Etymological Study of the Term "Zhongshu (Heatstroke)" - Yuhao HE; Bangxian ZHU; Lili LIU; Qi YANG; Ming LI (Yixue yu zhexue)
In order to systematically sort out the names related to Zhongshu (heatstroke), the authors conducted a systematic study of ancient Chinese medical literature and identified a total of 21 related terms. The earliest name of the disease appeared in Huangdi Neijing. In the Eastern Han Dynasty, Zhang Zhongjing classified Zhongye (an early term for heatstroke) as an independent disease, but the term "Zhongshu (heatstroke)" did not appear until the Southern Qi Dynasty. With the gradual refinement of medical theory during the Sui and Tang dynasties, Zhongshu (heatstroke) was systematically categorized, with corresponding treatment principles, methods and prescriptions. During the Song, Yuan and Ming dynasties, the meaning of Zhongshu (heatstroke) and the treatment system were gradually enriched and clarified, and targeted treatment methods were proposed for the elderly, laborers, women and young children respectively. In the Ming and Qing dynasties, theoretical research and treatment of Zhongshu (heatstroke) were gradually improved. In modern times, Zhongshu (heatstroke) has been classified as a legal occupational disease, with growing efforts toward its prevention. The development and enrichment of the disease name Zhongshu (heatstroke) reflects not only the change in the way the ancients understood the disease, but also the continuous development of Chinese medicine's understanding of the disease.